Europe's quest for technology sovereignty: Opportunities and pitfalls - Matthias Bauer; Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2020)
Covid-19 and its broader implications have highlighted the importance of Europe's digital transformation to ensure Europeans' social and economic well-being. It provides important new learnings about Europe's quest for "technology sovereignty". While the debate about technology sovereignty is timely, the precise meaning of sovereignty or autonomy in the realm of technologies remains ambiguous. It should be noted that the political discussions about European technology sovereignty emerged far before the outbreak of the Coronavirus. The European Commission's recently updated industrial and digital policy strategies "institutionalised" different notions of sovereignty, reflecting perceptions that more EU action is needed to defend perceived European values and to secure Europe's industrial competitiveness. Often the political rhetoric reflected perceptions that Europe is losing global economic clout and geopolitical influence. It was said that dependency on technological solutions, often originating abroad, would require a European industrial and regulatory response. Against this background, the Corona crisis provides two important lessons for EU technology policymaking.
Keywords: 330; Informationstechnik; Souveränität; Digitalisierung; EU-Forschungspolitik; Coronavirus; Wirtschaftskrise; EU-Staaten